2019
DOI: 10.1016/j.jcct.2018.09.010
|View full text |Cite
|
Sign up to set email alerts
|

Association of endogenous sex hormone levels with coronary artery calcium progression among post-menopausal women in the Multi-Ethnic Study of Atherosclerosis (MESA)

Abstract: Background: Sex differences in the incidence and manifestation of cardiovascular disease (CVD) suggest the involvement of sex hormones in disease pathogenesis. Coronary artery calcium (CAC) and its progression, measured by non-contrast cardiac computed tomography, are markers of subclinical atherosclerosis and predict CVD, even among low-risk women. We hypothesized that sex hormone levels were associated with CAC progression among women in the Multi-Ethnic Study of Atherosclerosis. Methods: We studied 2,759 … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
45
0
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
8
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 66 publications
(47 citation statements)
references
References 45 publications
(61 reference statements)
1
45
0
1
Order By: Relevance
“…[22] Despite some debates about the relationship between CAC and atherosclerosis, CAC and its progression are markers of subclinical atherosclerosis. [24] Repeat CAC scanning has been proposed as a method to track progression of total atherosclerosis burden and CAC progression correlates with worsening atherosclerosis. [25]…”
Section: Discussionmentioning
confidence: 99%
“…[22] Despite some debates about the relationship between CAC and atherosclerosis, CAC and its progression are markers of subclinical atherosclerosis. [24] Repeat CAC scanning has been proposed as a method to track progression of total atherosclerosis burden and CAC progression correlates with worsening atherosclerosis. [25]…”
Section: Discussionmentioning
confidence: 99%
“…Several seminal studies reported that post-menopausal estrogen treatments may reduce the risk of cardiovascular calcification when administered within the first 5 years of menopause (55, 56). While several recent studies suggest that initiation of estrogen repletion outside of this time period may not confer optimal protection against a myriad of CV complications, the timing, type, and dosing regimens of estrogen that confer vasculo-/valvulo-protection remains a very active field of investigation (57, 58).…”
Section: Role Of Estrogens In the Regulation Of Cardiovascular Calcifmentioning
confidence: 99%
“…These results suggest that there may be different mechanisms leading to progression of CIMT compared to CAC, and that these processes may be distinct from those affecting autonomic reflex to metabolic challenge. Although there are several large observational and randomised studies that investigated cardiovascular risk factors associated with the development of CIMT and CAC in women, none have taken into consideration pregnancy history . A simple, validated questionnaire is available to obtain pregnancy history .…”
Section: Pregnancy Historymentioning
confidence: 99%